Web‐based integrated bipolar parenting intervention for parents with bipolar disorder: a randomised controlled pilot trial. (16th May 2017) - Jones, Steven H.; Jovanoska, Jelena; Calam, Rachel; Wainwright, Laura D.; Vincent, Helen; Asar, Ozgur; Diggle, Peter J.; Parker, Rob; Long, Rita; Sanders, Matthew; Lobban, Fiona
Abstract : Background: People with bipolar disorder (BD) experience additional parenting challenges associated with mood driven fluctuations in communication, impulse control and motivation. This paper describes a novel web‐based self‐management approach (Integrated Bipolar Parenting Intervention; IBPI) to support parents with BD. Method: Parents with BD with children aged 3–10 years randomised to IBPI plus treatment as usual (TAU) or waitlist control (WL). IBPI offered 16 weeks access to interactive self‐management information concerning BD and parenting issues. Feasibility was through recruitment, retention and web usage. Clinical outcomes were assessed at baseline, 16, 24, 36 and 48 weeks. Trial Registration Number: ISRCTN75279027. Results: Ninety seven participants were recruited with 98% retention to end of intervention and 90% to final follow‐up (56%–94% data analysed of retained participants; higher rates for observer measures). 77% of IBPI participants accessed the website (53% accessed parenting modules). Child behaviour, parenting sense of competence and parenting stress improved significantly in IBPI compared to WL to end of intervention, sustained to 48 weeks. Impacts of IBPI on family functioning, parent mood and time to mood relapse were not significant. Conclusions: Online self‐management support for parents with BD is feasible, with promising improvements in parenting and child behaviour outcomes. A definitive clinical and cost‐effectiveness trial is required to confirm and extend these findings.